(untitled) (Raparin Journal of Humanities (RJH), 2026)
This study examines the impact of drone technology on the operational capabilities of armed non-state actors (ANSAs) in the Middle East, following 2010; the Middle East entered a new era of conflict, the escalations led to the appearance of new terrorist groups like Islamic state in Iraq and Syria (ISIS), and regional competition led to increased involvement of armed groups in the conflicts. Drone technology has extensively contributed to these conflicts through armed non-state actors in the region. The research focuses specifically on Hezbollah and ISIS in drone warfare. It explores how the adoption of unmanned aerial vehicles (UAVs) has reshaped traditional paradigms of asymmetric warfare by enhancing reconnaissance, precision strike capabilities, and long-range operations. The research has conducted a comparative analysis between both groups in terms of when Hezbollah, supported by state sponsorship, has developed a structured and technologically sophisticated drone program, whereas ISIS has employed an improvisational, low-cost approach aimed at disrupting enemy forces through innovative tactics. The research indicated how drone technology has significantly increased their reach and precision in targeted strikes, highlighting their ability to project power and adapt to evolving battlefield conditions. Ultimately, the increasing accessibility and deployment of drone technology by (ANSAs) in conflict zones, particularly in the Middle East, poses significant challenges to traditional security paradigms and necessitates a deeper understanding of its impact on asymmetric warfare. The aim of the study is to answer the question of how have Hezbollah and ISIS utilized drone technology to reshape their operational capabilities and asymmetric warfare strategies in the Middle East? The study underscores the growing need for flexible security policies in response to the proliferation of drones beyond state control and their integration into hybrid and irregular warfare strategies.